Extremal Trees with respect to Number of (A,B,2C)-Edge Colourings - Krzysztof Piejko (Journal of Applied Mathematics)
We determine the smallest and the largest number of (A,B,2C)-edge colourings in trees. We prove that the star is a unique tree that maximizes the number of all of the (A,B,2C)-edge colourings and that the path is a unique tree that minimizes it.